PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN ( Studi Pada Penumpang Bus PO. Shantika Jurusan Jepara - Jakarta ) - Febrian Rangga Saputra, 08.05.51.0021; Irsad, Moch. (Students Journal of Economic and Management, 2012)
Inthe era of competition in the business world that is increasingly tight, demanding business people should be able to maximize the performance of the company in order to compete in the marketplace. One of them is to improve the quality of service and pricing to achieve customer satisfaction. The better the quality of service and price is given it will increase customer satisfaction. The study, entitled